2009
DOI: 10.5194/os-5-193-2009
|View full text |Cite
|
Sign up to set email alerts
|

A new assessment of the error budget of global mean sea level rate estimated by satellite altimetry over 1993–2008

Abstract: Abstract. A new error budget assessment of the global Mean Sea Level (MSL) determined by TOPEX/Poseidon and Jason-1 altimeter satellites between January 1993 and June 2008 is presented using last altimeter standards. We discuss all potential errors affecting the calculation of the global MSL rate. We also compare altimetry-based sea level with tide gauge measurements over the altimetric period. Applying a statistical approach, this allows us to provide a realistic error budget of the MSL rise measured by satel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
168
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(185 citation statements)
references
References 31 publications
4
168
0
5
Order By: Relevance
“…The uncertainty range (1 standard deviation) comes from fitting a linear trend to the data using uncertainties on the annual averages of 5 mm and is consistent with an updated error budget of altimeter sea-level trend uncertainties (Ablain et al 2009). They estimate the largest uncertainties are related to the wet tropospheric (atmospheric water vapour) correction, the bias uncertainty of successive missions, orbit uncertainty and the sea-state bias correction.…”
Section: Gmsl (Mm)supporting
confidence: 66%
“…The uncertainty range (1 standard deviation) comes from fitting a linear trend to the data using uncertainties on the annual averages of 5 mm and is consistent with an updated error budget of altimeter sea-level trend uncertainties (Ablain et al 2009). They estimate the largest uncertainties are related to the wet tropospheric (atmospheric water vapour) correction, the bias uncertainty of successive missions, orbit uncertainty and the sea-state bias correction.…”
Section: Gmsl (Mm)supporting
confidence: 66%
“…Recent studies based on these observations showed that sea level is rising at a global mean rate of 3.3 mm yr −1 since 1993 (e.g. Ablain et al, 2009;Cazenave and Llovel, 2010;Nerem et al, 2010). They showed as well that sea level does not rise uniformly but displays strong regional variability (see Fig.…”
Section: Introductionmentioning
confidence: 92%
“…It is a global, homogenous, intercalibrated dataset based on global crossover adjustment (Le Traon and Ogor, 1998) using Topex/Poseidon and then Jason 1 as reference missions. It is corrected for the long wavelength orbit errors , ocean tides, and wet/dry troposphere and ionosphere (see Ablain et al, 2009 for more details). The inverted barometer (IB) correction has also been applied in order to minimize aliasing effects (Volkov et al, 2007) through the MOG2D barotropic model correction that includes the dynamic ocean response to short period (<20 day) atmospheric wind and pressure forcing and the static IB correction at periods above 20 day (see Carrere and Lyard, 2003 for details).…”
Section: Satellite Altimetry Sea Level Data (1993-2009)mentioning
confidence: 99%
“…Cazenave and Nerem, 2004) was somewhat unexpected. Due to a careful monitoring of error sources (see Ablain et al, 2009 for a recent review) and a continuous validation with tide gauge observations (e.g. Mitchum, 1998), the global mean sea level variations can now be monitored from space with T/P and its successors Jason-1 and Jason-2.…”
Section: Topex/poseidon: Large-scale Variability Is Observed For the mentioning
confidence: 99%